2020
DOI: 10.1088/1742-6596/1521/4/042105
|View full text |Cite
|
Sign up to set email alerts
|

Student’s research skills in middle school of Kuningan district

Abstract: This exploratory study aimed to analyze the research skills and to explore the authentic research abilities that can support students’ research skills. The study engaged sixty-eight students of science class from two schools in Kuningan district. The data was collected through research skills tests, consist of 11 items of essay questions including seven components of research skills: 1) Understanding phenomena and identifying problems, 2) formulating problems, 3) composing hypotheses, 4) making research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The achievement of research skill competencies in Indonesia at the secondary and higher education levels is still relatively low, which is confirmed by research conducted by Sari et al (2019); Roito et al (2019);and Nurlaelah et al (2020) with the conclusion that students still lack mastery of research procedures, implementation, and reporting. At the university level, the mastery of research skills is low, especially in the aspect of intellectual ability (Aripin et al, 2021), the implementation stage of research (Solihat, 2015;Maknun et al, 2020), and research data analysis (Subekti et al, 2018).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…The achievement of research skill competencies in Indonesia at the secondary and higher education levels is still relatively low, which is confirmed by research conducted by Sari et al (2019); Roito et al (2019);and Nurlaelah et al (2020) with the conclusion that students still lack mastery of research procedures, implementation, and reporting. At the university level, the mastery of research skills is low, especially in the aspect of intellectual ability (Aripin et al, 2021), the implementation stage of research (Solihat, 2015;Maknun et al, 2020), and research data analysis (Subekti et al, 2018).…”
Section: Introductionmentioning
confidence: 75%
“…The research skill method mainly was used the inquiry method (Azizah & dan Parmin, 2012); (Craig & Bielenberg, 2015); (Chu, 2008); (Rodríguez et al, 2019); project-based learning (Maknun et al, 2019); (Maskall & Cotterell, 2011), (Prahmana, 2015), Step-by-Step-model (Roito et al, 2019); Research skills training (Gyuris, 2018); personal reflection (Solihat, 2015); practicum (Nurlaelah et al, 2020); experiments (Sabirova & Zakirova, 2015); virtual laboratory (Bortnik et al, 2017); game-based learning (Abbott, 2019); experience study (Subekti et al, 2018). A total of two studies were carried out at the elementary school level (Sabirova & Zakirova, 2015); (Chu, 2008); one research at the junior high school level (Nurlaelah et al, 2020) and one research at the high school level (Roito et al, 2019), the rest were carried out in universities. The distribution of the effect of the methods used in this research is shown in table 1 with low impact (Nurlaelah et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, KPS is very important to be trained in learning, because KPS is an ability that scientists use while working and also a competency needed when solving scientific problems [17]. Research skills help students to critically investigate problems, produce, and evaluate relevant data, test ideas, theories, and hypotheses, and successfully guide the way for them to navigate the sea of information that characterizes the era information [12].…”
Section: Resultsmentioning
confidence: 99%